2012
DOI: 10.1111/j.1468-0416.2012.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Rating Agencies as Gatekeepers to the Capital Market: Practical Implications of 40 Years of Research

Abstract: This paper gives an extensive overview on the avenues academic research has taken in exploring the role of credit ratings. In doing so, it relies on a strict methodological approach for the collection and evaluation of relevant studies to address the criticisms on the lack of profoundness in prior literature reviews in business research. It provides therefore to both academics and practitioners an exhaustive compendium on the role and relevance of credit ratings for each key stakeholder over the past 40 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 274 publications
(413 reference statements)
0
11
0
3
Order By: Relevance
“…For those studies that in fact discuss the effect of country characteristics for certain FDI modes, Hyun and Kim () observe that greenfield investments have caught the primary academic attention, while M&A have lagged behind. Apart from complementing the extant research in this respect, the results of this paper simultaneously enrich the so far sparse literature body on the direct impact of credit ratings on corporations (Lagner and zu Knyphausen‐Aufseß, ). Here, the insights will be of particular interest to acquisitive companies or prospective targets, especially in countries with instable rating situations.…”
Section: Introductionmentioning
confidence: 57%
“…For those studies that in fact discuss the effect of country characteristics for certain FDI modes, Hyun and Kim () observe that greenfield investments have caught the primary academic attention, while M&A have lagged behind. Apart from complementing the extant research in this respect, the results of this paper simultaneously enrich the so far sparse literature body on the direct impact of credit ratings on corporations (Lagner and zu Knyphausen‐Aufseß, ). Here, the insights will be of particular interest to acquisitive companies or prospective targets, especially in countries with instable rating situations.…”
Section: Introductionmentioning
confidence: 57%
“…This paper concluded that there is strong relationship between the interest rate and capital flow. Lagner and Knyphausen-Aufseß (2012), investigated the practical approach towards the capital and money market. This paper explains the relationship between the money market and capital market.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to their last point, Frost () conducts a detailed review and evaluation of the criticisms that rating agencies faced particularly in the aftermath of the corporate accounting scandals of the early 2000s (such as Enron). Only recently, Lagner and zu Knyphausen‐Aufseß () have offered an extensive discussion of the literature on the role of credit rating agencies in relation to their different stakeholders. They conclude that “[t]he academic debate particularly missed to explore the impact of credit ratings on its stakeholders” (p. 186) and point to the influence of corporate ratings on companies’ strategic decisions as a highly relevant direction for future research.…”
Section: Introductionmentioning
confidence: 99%